METAL WELDING TRAINING FOR SKILLS PROVISION FOR MECHANICAL ENGINEERING EDUCATION STUDENTS, PALANGKA RAYA UNIVERSITY - Jhonni Rentas Duling; Topan Eka Putra (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2021)
Community empowerment activities in general aim to form individuals and communities to become independent. Independence is a condition experienced by a person which is characterized by the ability to think, decide and do something that is deemed appropriate in order to achieve solving the problems faced by using the power/ability possessed. The training activities aim to equip participants with metal welding skills. The activity was carried out at the Mechanical Engineering Education Laboratory, FKIP UPR. The purpose of these activities is in line with the higher education functions and objectives mandated in Law no. 12 of 2012 Article 4 paragraph 3; namely to